Kontribusi Filosof Muslim Dalam Pengembangan Sains : Tinjauan Islam - Nurhilaliyah (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This study aims to examine the thoughts of Al-Khawarizmi in the development of mathematics and its relationship with Islamic values during the Abbasid era. The research employs a literature study method by reviewing classical and modern sources related to his biography, works, and ideas. The analysis is conducted using a descriptive-historical approach to understand his contributions to science and the practical life of Muslims. The results show that Al-Khawarizmi played a significant role in laying the foundations of algebra, algorithms, and the modern numeral system, as well as contributing to astronomy and geography that support religious practices. His thinking reflects the integration of science and religion, where the pursuit of knowledge is considered part of faith. Furthermore, his ideas remain relevant in education and the development of modern science, particularly in shaping logical and systematic thinking, as well as their application in information technology. This study highlights the importance of preserving the scientific legacy of Muslim scholars through the integration of science and Islamic history in education, in order to encourage younger generations to contribute to global scientific advancement.